The Influence of Leadership Style and Organizational Climate on Teacher Job Satisfaction in Madrasah Tsanawiyah Negeri 1 Batang Hari - Muhammad Yusup; Marzani Marzani; Iwan Aprianto; Gitty Loviani (P3M IAI Nusantara Batang Hari, 2022)
This study aims to determine the effect of leadership style and organizational climate on teacher job satisfaction at Madrasah Tsanawiyah Negeri 1 Batang Hari. This was a quantitative research with a survey approach. The population of this study is the number of all teachers who teach at Madrasah Tsanawiyah Negeri 1 Batang Hari. Multiple regression analysis was used to analyze the data and processed by the SPSS Version 20.0 program. The results showed that leadership style had a significant effect on job satisfaction with t count > t table (5.541 > 1.693). This indicated that Ha was rejected and H0 was accepted. Additionally, organizational climate has a significant effect on job satisfaction by obtaining a value of t count> t table (3.491> 1.693). This indicated that Ha was rejected and H0 was accepted. This mainly meant that partially there was a significant effect between leadership style and organizational climate on job satisfaction. With the results of the coefficient of determination (r square) of 0.961, it meant that the leadership style and organizational climate variables were able to increase job satisfaction decisions by 96.1% and 0.039 or 3.9% were residual variables with a significant effect.